1997
DOI: 10.1021/es970023m
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Coproducts of Commercial Linear Alkylbenzene Sulfonate

Abstract: Dialkyltetralin sulfonate (DATS) and single methyl-branched isomers of linear alkylbenzene sulfonate (iso-LAS) are coproducts that together can range from 1 to 10% of commercial LAS depending on the manufacturing process. Biodegradation studies using radiolabeled DATS and iso-LAS showed mineralization by indigenous microbial populations in laboratory simulations of aquatic and soil environments. Half-lives ranged from 2 to 20 days, which is rapid enough to suggest that accumulation would not occur in these env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
3
22
1
Order By: Relevance
“…Others have reported on the complexity in the measurement of LAS biodegradation intermediates which cause difficulties in biodegradation analysis (Holt et al, 1995;Trehy et al, 1996;Crescenzi et al, 1996;Federle et al, 1997;Mampel et al, 1998;Krueger et al, 1998). A study by Nielsen et al (1997), confirmed that LAS was completely degraded in wastewater treatment plants. Trehy et al (1996) reported that the removal from four activated sludge systems averaged 99.5% for LAS and 99.1% for LAS intermediates.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Others have reported on the complexity in the measurement of LAS biodegradation intermediates which cause difficulties in biodegradation analysis (Holt et al, 1995;Trehy et al, 1996;Crescenzi et al, 1996;Federle et al, 1997;Mampel et al, 1998;Krueger et al, 1998). A study by Nielsen et al (1997), confirmed that LAS was completely degraded in wastewater treatment plants. Trehy et al (1996) reported that the removal from four activated sludge systems averaged 99.5% for LAS and 99.1% for LAS intermediates.…”
Section: Introductionmentioning
confidence: 90%
“…Linear alkyl benzene sulfonate (LAS) was introduced in 1965 as a biodegradable alternative to non-biodegradable branch-chained alkyl benzene sulfonates (ABS) and since has become the common anionic surfactant in commercial detergent formulations. For example, in 1994, 950,000 metric tons of LAS were used in Europe, North America, and Japan alone (Nielsen et al, 1997). Trehy et al (1995) reported environmental LAS concentrations in the influent (3.0 -7.7 mg/L) and effluent (0.003 -0.086mg/L) of the activated sludge process from 10 U.S. domestic wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is generally known that synthetic detergent made from linear alkyl benzene (LAB) has better biodegradability than that made from BAB or natural soap. 5 The phenyl group position of LAB has an effect on its surfaceactive property and biodegradability of linear alkyl benzene sulfonate (LAS). Among the isomers of LAB, 2-LAB exhibits the highest biodegradability, making it dominant detergent intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…As LAS is used as a detergent agent, it mainly enters the environment via industrial and domestic sewage (Krueger et al 1998b). Significant quantities of LAS co-products, like dialkyhetralin sulphonates and LAS with single methyl branching on the alkyl chains (iso-LAS), can be found in sewage too (Nielsen et al 1997). The removal and degradation of LAS and co-products already start when entering the sewer system (Moreno et al 1990, Holt et al 1998.…”
Section: Remediation Possibilitiesmentioning
confidence: 99%
“…At present, the most effective methods for the remediation of sewage contaminated by LAS are municipal and industrial wastewater treatment plants based on aeration/settling, activated sludge/aerobic digestion of sludge, or activated sludge/anaerobic digestion of sludge (Berna et al 1989). LAS and co-products entering the treat-ment plants through the sewage influents are degraded up to 99.7% of the influent concentrations (Berna et al 1989, Field et al 1992, Nielsen et al 1997, Waters et al 2000, with half-lives in the range of 1-2 days for activated sludge (Krueger et al 1998b). LAS and most of the co-products undergo extensive mineralization (>50 %) and ultimate biodegradation (80-90% mineralization plus conversion to biomass), but release some (10-20%) of their carbons as water-soluble intermediates (Nielsen et al 1997).…”
Section: Remediation Possibilitiesmentioning
confidence: 99%